A review of the potential utilisation of plastic waste as adsorbent for removal of hazardous priority contaminants from aqueous environments. (March 2020) - Zhang, Huiyi; Pap, Sabolc; Taggart, Mark A.; Boyd, Kenneth G.; James, Neil A.; Gibb, Stuart W.
Abstract: There is growing global awareness of the presence and negative impacts of waste plastic in the marine environment. Risks to wildlife include ingestion and entanglement for macro-plastic (larger than 5 mm in length), alongside food chain transfer for micro-plastics (less than 5 mm in length). Plastics in the marine environment have also been shown to adsorb and accumulate contaminants from seawater, e.g., heavy metals and hydrophobic organic compounds. This means that plastics can additionally act as vectors for transport of contaminants, permitting ecotoxicological risks to be spatially extended. However, the ability of waste plastic to adsorb pollutants also offers potential opportunity, if they can be used for the decontamination of wastewater. Here, we provide an overview of marine plastic types and distribution, and then systematically assess their potential to be repurposed as novel adsorbents. Data published in recent years are interrogated to gain an overview of the interaction mechanisms between marine plastics and both organic and inorganic contaminants. In addition, factors that may be exploited to enhance their performance in removal of contaminants are also reviewed and prioritised, e.g., surface modification and activation. This paper highlights the novel potential of repurposing plastic waste for wastewater treatment applications and seeks to identify key knowledge gaps and future research priorities for scientists and engineers. Graphical abstract: Image 1 Highlights: The global use of plastic has resulted in plastic waste becoming a major issue in the environment. Marine plastic waste can act as a vector for pollutants in aquatic systems. The mechanisms of pollutant adsorption are complex and require further exploration. SEM-EDX, BET, FTIR and XRD can be used to explore mechanisms. Future studies should consider the potential utilisation of plastic waste as an adsorbent.